Bullying Portrayed in Mean Girls Movie - Nun Ayu Waya Sirly; Nine Febrie Novitasari (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2017)
Bullying is such a key problem in our schools and society because it impacts a large number of students of all races, genders, and socioeconomic statuses. Here the researcher identified types of bullying and described impacts of bullying in Mean Girls Movie. The data were in the form of utterances and actions implicated bullying in Mean Girls Movie. The steps to analyze the data were: identifying and classifying data based on the types of bullying used by The National Centre Againts Bullying (2010) and psychoanalysis from Freud (1973) in Storey (2009:91), describing impacts of bullying using theory of Righby (2003) in Darmawan (2010:23), and making conclusion based on the types and impacts of bullying in the Mean Girls Movie. The findings of the analysis reveal that there were twelve data which covered: four verbal bullying, one physical bullying, two psychological bullying, and five social bullying. Meanwhile, for the impacts of bullyings to the characters who get bullied, the researcher found low psychological well-being, poor social adjustment, and no response to the bullyings. The researcher expects the next researchers to do the analysis on bullying with other object of research and different relevant theories.